2022
DOI: 10.1136/bmjopen-2021-059204
|View full text |Cite
|
Sign up to set email alerts
|

Medicines prescribed by non-medical independent prescribers in primary care in Wales: a 10-year longitudinal study April 2011–March 2021

Abstract: ObjectivesThe therapeutic classes of medicines prescribed by non-medical independent prescribers (NMIPs) working in primary care in Wales has not been studied in detail. The aim of this study was to conduct a 10-year longitudinal analysis of NMIP prescribing in Wales from April 2011 to March 2021. The study examined the British National Formulary (BNF) chapters from which medicines were prescribed by NMIPs, whether this changed over time, and whether there was variation in prescribing across the geographic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Similarly, a study in Wales conducted over a 10-year period (April 2011 to March 2021) analyzed prescribing by non-medical independent prescribers. They found that substances from seven groups of the BNF classification-cardiovascular, the nervous system, infections, the respiratory system, the endocrine system, the gastrointestinal system, and skin-accounted for about 80% of all prescriptions, with cardiovascular drugs being the dominant group [28,29]. These were also the groups of substances most frequently prescribed by pharmacists in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, a study in Wales conducted over a 10-year period (April 2011 to March 2021) analyzed prescribing by non-medical independent prescribers. They found that substances from seven groups of the BNF classification-cardiovascular, the nervous system, infections, the respiratory system, the endocrine system, the gastrointestinal system, and skin-accounted for about 80% of all prescriptions, with cardiovascular drugs being the dominant group [28,29]. These were also the groups of substances most frequently prescribed by pharmacists in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Compared to other published research from the United Kingdom and parts of Europe, these medications differ from what was most commonly reported as prescribed by pharmacists, which included cardiovascular, nervous system, respiratory system, and infectious diseases medications. 33 , 34 Given differences across countries in when independent prescribing for pharmacists began, and related differences in approved conditions for prescribing, this is not unexpected. Many research studies have demonstrated the efficacy and safety of pharmacist prescribing 35 , 36 for conditions such as uncomplicated cystitis, with demonstrated patient satisfaction with this practice.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported irrational use in broad treatment categories but did not indicate the drugs associated with irrational use nor describe dose modification as the reason for irrational use. 4 6 , 16 , 23 This practice of dose modification causes higher pill burden and has implications for patients’ adherence to treatment due to confusion, frustration, and doubting the effectiveness of treatment caused by the number of pills prescribed. 17 , 24 These factors can lead to poor compliance to drug treatment and affect quality of life from increased morbidity and mortality in patients with NCDs.…”
Section: Discussionmentioning
confidence: 99%